Regulation of Brain-Derived Neurotrophic Factor Exon IV Transcription through Calcium Responsive Elements in Cortical Neurons - Zheng, Fei; Zhou, Xianju; Luo, Yongneng; Xiao, Hua; Wayman, Gary; Wang, Hongbing (PloS one, 2011)
Activity-dependent transcription of brain-derived neurotrophic factor (BDNF) has been studied as an important model to elucidate the mechanisms underlying numerous aspects of neuroplasticity. It has been extensively emphasized that Ca(2+) influx through different routes may have significantly different effects on BDNF transcription. Here, we examined the regulatory property of the major calcium responsive elements (CaRE) in BDNF promoter IV in cultured rat cortical neurons. BDNF promoter IV, as well as CaRE1 and CaRE3, was significantly activated by Ca(2+) influx through L-type voltage-gated calcium channel (L-VGCC) or NMDA receptor (NMDAR). However, the L-VGCC- and NMDAR-mediated activation of CaRE was differentially regulated by different Ca(2+)-stimulated protein kinases. Specifically, PKA, CaMKI, and CaMKIV activity were required for L-VGCC-, but not NMDAR-mediated CaRE1 activation. CaMKI activity was required for NMDAR- but not L-VGCC-mediated CaRE3 activation. Surprisingly, the activation of CaRF, a previously identified transcription factor for CaRE1, was stimulated via L-VGCC but not NMDAR, and required MEK, PI3K and CaMKII activity. These results suggest a new working model that activity-dependent BDNF IV up-regulation may be coordinately mediated by CaRE1 and CaRE3 activity, which show different responses to Ca(2+)-stimulated kinases. Our data also explain how the individual cis-element in BDNF promoter is distinctively coupled to different Ca(2+) routes.